Inclusive Education in the 21st Century: Parameters and Opportunities for Learners with Special Needs - Jacob, Udeme Samuel; Olisaemeka, Angela Nneka (European Scientific Journal, ESJ, 2016)
This paper examined parameters and opportunities for learners with special educational needs in an effective inclusive education as it relates to 21st century. It differentiated inclusive education from mainstreaming and integration and went further give a comprehensive meaning to the term inclusive education. Some of the benefits of this inclusive education are multicultural learning environment, socialization and the development of the child. Parameters identified for effective inclusive education are placing the child in age appropriate grade place, no special classes or schools and cooperative learning practiced where teachers can share ideas for improvement of the educational system. Conclusion was made on the need for inclusive education.